Magnetic Resonance Imaging of Graded Skeletal Muscle Injury in Live Rats. (January 2014) - Cutlip, Robert G.; Hollander, Melinda S.; Johnson, G. Allan; Johnson, Brice W.; Friend, Sherri A.; Baker, Brent A.
Introduction: Increasing number of stretch-shortening contractions (SSCs) results in increased muscle injury. Methods: Fischer Hybrid rats were acutely exposed to an increasing number of SSCs in vivo using a custom-designed dynamometer. Magnetic resonance imaging (MRI) imaging was conducted 72 hours after exposure when rats were infused with Prohance and imaged using a 7T rodent MRI system (GE Epic 12.0). Images were acquired in the transverse plane with typically 60 total slices acquired covering the entire length of the hind legs. Rats were euthanized after MRI, the lower limbs removed, and tibialis anterior muscles were prepared for histology and quantified stereology. Results: Stereological analyses showed myofiber degeneration, and cellular infiltrates significantly increased following 70 and 150 SSC exposure compared to controls. MRI images revealed that the percent affected area significantly increased with exposure in all SSC groups in a graded fashion. Signal intensity also significantly increased with increasing SSC repetitions. Discussion: These results suggest that contrast-enhanced MRI has the sensitivity to differentiate specific degrees of skeletal muscle strain injury, and imaging data are specifically representative of cellular histopathology quantified via stereological analyses.